A rare case of basaloid squamous cell carcinoma in the labial commissure region with literature review - Gabriela Moura Chicrala; Raquel D'Aquino Garcia Caminha; Silas Antonio Juvencio de Freitas Filho; Denise Tostes Oliveira; Paulo Sérgio da Silva Santos (Oral Oncology Reports)
Basaloid squamous cell carcinoma (BSCC) is a rare variant of oral squamous cell carcinoma (SCC), representing less than 1% of all SCC in the mouth. Despite being similar to the conventional SCC regarding etiological factors and clinical presentation, the clinical course and prognosis of BSCC remain controversial in the literature. Although the microscopic aspects of the BSCC are well defined, its accurate diagnosis might be a challenger for the pathologist, especially regarding the quality and quantity of the analyzed fragment, being extremely relevant to considering possible differential diagnoses. We describe a rare case of an 83-year-old male who presented a rapidly growing lesion in the labial commissure, asymptomatic and extending to the buccal mucosa, resulting in a peculiar clinical presentation. Histopathological examination of incisional biopsy revealed neoplastic epithelial cells with moderate pleomorphism, figures of mitosis, foci of comedonecrosis, invading the submucosa and skeletal striated muscle tissue, confirming BSCC diagnosis. We also present a discussion on the clinical aspects, differential diagnosis, staging, and evolution, and in addition a relevant summary of reported BSCC clinical cases in recent literature.